Factors of spatial distribution of forest floor properties in the Jizerské Mountains - L. Borůvka; L. Mládková; O. Drábek; R. Vašát (Plant, Soil and Environment, 2005)
The aim of this contribution was to describe spatial distribution of soil characteristics of forest floor in the JizerskéMountainsregion and to assess the effect of stand factors by means of geostatistics, using structural correlation coefficients. Most soil properties showed a low spatial dependence with variogram range of 6000 m. Kriged maps of spatial distribution of soil properties were created. Most characteristics were influenced by altitude. A general decrease of pH and Ca and Mg content and an increase of potentially toxic Al forms (AlKCl) due to high S and N loading were demonstrated. An effect of liming on the decrease of AlKCl content, and higher pH and Mg content and lower AlKCl under beech forest were shown. Lower acidity and a better humus quality were found at higher altitudes under grass coverin spite of high S and N content. The ratios S/Ca and S/(Ca + Mg) can serve as an indicator of soil acidification level.